Effect of cement on the stability and the wearrance of soils in earthworks - Karam Feth-Allah Bendimerad; Abdeldjalil Zadjaoui (MATEC Web of Conferences, 2018)
The technique of soil treatment is known for a long time, currently, during the big motorway programs this technique is experiencing important to reach zero imprints and zero deposit in a context of sustainable development or the socio-economic and environmental challenges incite during the work of earthworks. Our work puts highlights the treatment of fine soils in westerns region of Algeria (wilaya of Tlemcen, a project to construct a payment station for the entry of the wilaya (sample n°1), electrical post 400/200 KVA in the locality Ain Fetah (sample n°2)), belonging to the class A3h (very plastic clay) according to the Technical Guide for Earthworks (GTR), whose use in the raw state would involve great risks of stability because of their plasticity (Ip > 20%) and their low capacity (CBR < 25) according to the Specification of the Algerian Loads, Technical Clauses (CSDCA-CT) by the incorporation of the stabilizing agents, for example the variant of locally manufactured CEM II / A42.5N composite cement, in order to define their behaviours by examining the variation of their characteristics determined according to the Algerian standards and at a ambient temperature according to the additive dosage and to contribute to the deduction of the interest of the method demonstrated previously. The results obtained clearly show a tendency the rearrange classification of the soils studied according to the unified system en proportion whit to the additive dosage (0 to 14%) in view of the appreciable change in the plasticity behaviour, which results in a decrease in the plasticity index, going up to 37.7% and the 11% of the maximum dry density accompanied by a satisfactory increase in the suitability of the materials to be supported a load with different moisture content and changes in water regime exceeds 100%. Given the unavailability of other exploitable deposits near the site and the experimental results obtained, the variant of the treatment seems feasible.